EVALUATION OF PHYSIOLOGICAL, HAEMATOLOGICAL AND ETHOLOGICAL CHARACTERISTICS OF MITHUNS (Indian Journal of Animal Production and Management, 2016)
The study was carried on 20 Mithuns (3-5 years of age), irrespective of sex, 5 from each strain collected  from the States of Arunachal Pradesh (AR), Mizoram (MZ), Manipur (MN) and Nagaland (NL) at NRC  on Mithun, Medziphema, Nagaland. The values for physiological characteristics viz. body temperature,  rumen movement, heart rate and respiration rate did not vary in four strains of mithun. The values of  packed cell volume (PCV), haemoglobin (Hb), white blood cell (WBC), mean corpuscular volume (MCV)  and mean cell haemoglobin concentration (MCHC) did not vary in the four strains. The value of red blood  cell (RBC) was significantly (P< 0.01) higher in MZ and the lowest in MN strains while the values for MCH  was significantly (P< 0.01) higher in MN and lowest in MZ strains. The values for average grazing time  (GT), rate of grazing (GR), grazing intake (GI) and grazing cycle (GC) did not vary irrespective of strains  of mithun. The average values for time spent in mastication in minutes (TMC) was significantly (P< 0.05)  higher in MZ strain of mithun followed by MN, NL and the least in AR strain; however, the values did not  vary between MN and NL strains. The average values for mastication rate as jaw movement/ minute (MR)  was significantly (P< 0.05) higher in MZ strain of mithun followed by NL, MN and the least in AR strain;  however, the values did not vary among MZ, NL and MN strains. The values for average eating speed  of concentrate in second/kg (ECS) did not vary irrespective of strains of mithun. The average values for  different drinking behaviour viz. time spent in drinking (TD), numbers of drinks (ND), drinking speed (DS)  and numbers of sucking (NS) did not vary irrespective of strains of mithun. The average values for resting  behaviour in terms of time spent in lying down (TLD), loafing (TLO), idling (TID), rumination (TR), number  of rumination period (NRP), bites per bolus (BB), number of boluses (NB), boluses per rumination (BR)  and rumination speed (RS) did not vary irrespective of strains of mithun. From the study, it can be concluded that Mithuns have almost similar physiological and ethological  characteristics irrespective of different four strains. However, such study may be repeated with large sized  samples keeping the present investigation as a base-line work.
Keywords: Haemoglobin; Loafing; , Mastication; Rumen movement; Rumination and Boluses